2008
DOI: 10.1007/s10646-008-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a toxic cyanobacterial bloom and water hydrology on algal populations and macroinvertebrate abundance in the upper littoral zone of Lake Krugersdrift, South Africa

Abstract: The biological interactions and the physical and chemical properties of the littoral zone of Lake Krugersdrift were studied for a 4-month period when a dense, toxic cyanobacterial bloom dominated by Microcystis aeruginosa was present in the main lake basin. The presence of a toxic strain of M. aeruginosa was confirmed through the use of ELISA and molecular markers that detect the presence of the mcyB and mcyD genes of the mcy gene cluster that synthesizes microcystin. An increase in Microcystis toxicity at sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Ge´rard et al (2009) also found that bivalves were more sensitive to cyanobacterial bloom than pulmonates. Correspondingly, Oberholster et al (2009) observed that an increase in Microcystis toxicity at sites dominated by cyanobacterial scum was accompanied by an increase in the total abundance of Hirudinae, Chironomidae, and Tubificidae. From 1998 to 2007, algal blooms in Lake Taihu occurred at increasing frequency and with lengthened duration.…”
Section: Discussionmentioning
confidence: 87%
“…Ge´rard et al (2009) also found that bivalves were more sensitive to cyanobacterial bloom than pulmonates. Correspondingly, Oberholster et al (2009) observed that an increase in Microcystis toxicity at sites dominated by cyanobacterial scum was accompanied by an increase in the total abundance of Hirudinae, Chironomidae, and Tubificidae. From 1998 to 2007, algal blooms in Lake Taihu occurred at increasing frequency and with lengthened duration.…”
Section: Discussionmentioning
confidence: 87%
“…Alternatively, under the vicinity of hexavalent chromium, the production of pigment is blocked. This pigment production can be attributed due to the relationship between concentration of chromium and the generation of blue pigmentation by the bacterium (Arora 1966;Grizzle 1984;Paoletti 1999;Oberholster et al 2009;Jain et al 2010;Aslam et al 2012;Malik & Bharti 2012).…”
Section: Microbial Indicatorsmentioning
confidence: 99%
“…Toxic cyanobacteria are often reported to be the cause of mass mortality of aquatic organisms in the field. For example, in a 4 mo study, Oberholster et al (2009) observed that an increase in microcystins at sites dominated by cyanobacterial scum was accompanied by an in crease in the total abundance of the macroinvertebrate families Hirudinae, Chirono midae, and Tubi ficidae. Gérard et al (2009) observed that relative abundances of prosobranchs, pulmonates and bi valves were significantly different before and after a cyanobacterial bloom.…”
Section: Community Structure and Spatiotemporal Patternsmentioning
confidence: 99%